Efektifitas Pemberian Perasan Bawang Putih (Allium Sativum Linn) Dosis Tunggal Terhadap Jumlah Telur Cacing Gelang (Toxocara Canis) Secara In Vivo - Utami, Ratri Risky; Nuryati, Anik; Nuryani, Siti (Jurnal Teknologi Laboratorium, 2014)
Background this research is worm disease problematic in the field of health. Treatment for the disease worms that have been used are synthetic drugs that have side effects are not good for health and can lead to dependence. One of the medicinal plants used for deworming is garlic. Chemical constituents in garlic is allicin that is anthelmintics.To prove that it is carried out in vivo study using dogs infected with Toxocara canis worms as test animals.Objective this research to knowing of the effectiveness of various doses of garlic juice with a gift on the first day against Toxocara canis worm egg counts in vivo and the largest decrease in the effectiveness of Toxocara canis worm egg counts after administration of juice garlic at a dose of 0,5; 1 and 1,5 percent weight within 6 days of observation.Methods this research is an experimental study using dogs infected with Toxocara canis nearly the same number of eggs as well as the research design pretest-posttest with control group.Results the largest decrease in the effectiveness of Toxocara canis worm egg counts after administration juice garlic at a dose of 0,5; 1 and 1,5 percent weight within 6 days of observation known to occur on day 3 with a percentage of effectiveness are 48,49%; 67,18%; dan 82,85%. The higher doses of garlic juice, the more effective to decline in the amount of worm eggs Toxocara canis in vivo.Conclusion this research is garlic juice with various doses are not as effective as once treatment in reducing the the amount of eggs bracelet worm (Toxocara canis) in vivo.